Comparing Dung Beetle Species Assemblages Between Protected Areas and Adjacent Pasturelands in a Mediterranean Savanna Landscape - NUMA, CATHERINE; Verdú, José R; Rueda, Cristina; Galante, Eduardo (Rangeland Ecology & Management, 2012)
Dung beetles are considered keystone species because of their role in decomposition, seed dispersal, and control of vertebrate parasites in grazed habitats. Despite the ecological importance of this group to pasture ecosystem functioning, still little is known about its relationship with grazing management activities. We evaluated the conservation value of protected areas for dung beetle diversity by comparing two different management conditions of Mediterranean savanna in central Spain. Four different sites with wild herbivory (red deer, roe deer) were sampled inside the Cabañeros National Park, and four sites with traditional agrosilvopastoral management were sampled in a sheep farm near the park. The dung beetle species richness was similar between savanna conditions, but the total dung beetle abundance and biomass were considerably greater in the park grasslands than in the grasslands of the sheep farm. Dung beetle species composition, species dominance, and abundance by functional groups from both park and farm sites were different, despite the high similarity among the sampled sites in both hydric content and dung availability. Onthophagus maki (Illiger 1803) and O. furcatus (Fabricius 1781) were the dominant species in the park, while O. furcatus, Aphodius foetidus (Herbst 1783), and Caccobius schreberi L. were the dominant species on the farm. Species richness and abundance of telecoprids were higher in the park than on the farm. Abundance of paracoprids was also higher in the park than on the farm, while no differences in species richness and abundance of endocoprids were observed between both conditions. These results suggest that management activities such as plowing and the use of veterinary substances affect soil structure and dung quality and could be important factors that alter dung beetle assemblages in terms of composition, abundance, and biomass on traditional farms.
Keywords: land use; livestock management; natural protected areas; Scarabaeoidea; species diversity

Scaling local abundance determinants in mediterranean dung beetles - NUMA, CATHERINE; LOBO, Jorge M.; VERDÚ, JOSÉ R.; Uma, Catherine N. (Insect Conservation and Diversity, 2012)
Abstract. 1. We study the factors that contribute to the variation in the local abundance of dung beetle species inhabiting Cabañeros National Park, a Mediterranean reserve in Central Spain. The relative roles of five different groups of explanatory variables (climatic, local-scale vegetation, landscape-scale vegetation, landscape connectivity and trophic resources) were assessed for 27 sampling sites established by a nested hierarchical sampling design that considered three regional landscapes (woodland, scrubland, grassland) and three local habitat types (forest, scrub, pasture) within each landscape. 2. Connectivity variables related to the spatial configuration of closed vegetation and distance to patches of open or closed vegetation were the best predictors of the species abundance. Precipitation was the most important climatic variable, whereas grassland area at the local- or landscape-scale and woodland area at the landscape-scale were the most important vegetation variables. Dung resources variables had the lowest explanatory ability. 3. More than 60% of the models explained more than 70% of the total variability. Observed and predicted abundance were highly and positively correlated and the mean percentage of absolute predictive errors was approximately 50%. Low-abundance observations had higher predictive errors and model accuracies seemed to be lower for species with narrow distributional ranges and presence in a high number of sampling localities. 4. Mediterranean ecosystems contain a diverse assemblage of dung beetle species whose composition and abundance are influenced by a variety of factors operating across different spatial scales. The most important variables are the spatial configuration and the habitat connectivity around each locality.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Abundance models; Cabañeros National Park; landscape connectivity; landscape scale; Scarabaeoidea; species traits

Dung Beetles Eat Acorns to Increase Their Ovarian Development and Thermal Tolerance - Verdú, José R; Casas, José L; Lobo, Jorge M; NUMA, CATHERINE (PLoS ONE, 2010)
Animals eat different foods in proportions that yield a more favorable balance of nutrients. Despite known examples of these behaviors across different taxa, their ecological and physiological benefits remain unclear. We identified a surprising dietary shift that confers ecophysiological advantages in a dung beetle species. Thorectes lusitanicus, a Mediterranean ecosystem species adapted to eat semi-dry and dry dung (dung-fiber consumers) is also actively attracted to oak acorns, consuming and burying them. Acorn consumption appears to confer potential advantages over beetles that do not eat acorns: acorn-fed beetles showed important improvements in the fat body mass, hemolymph composition, and ovary development. During the reproductive period (October-December) beetles incorporating acorns into their diets should have greatly improved resistance to low-temperature conditions and improved ovarian development. In addition to enhancing the understanding of the relevance of dietary plasticity to the evolutionary biology of dung beetles, these results open the way to a more general understanding of the ecophysiological implications of differential dietary selection on the ecology and biogeography of these insects.
Keywords: Acorn consumption; Body condition (PG); dietary plasticity; Thorectes lusitanicus